Effect Of Good Corporate Governance On Tax Avoidance of The Company In Listed of The Indonesia Stock Exchange (Bei) - Rimi Gusliana Mais; Dewi Patmaningsih (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2017)
This study aimed to examine the effect of corporate governance on the extent of tax avoidance with proxy current etr. Elements of corporate governance that are used to test are institutional ownership, managerial ownership, independentcommissaryproportion,audit committee, and audit quality. This research uses descriptive quantitative approach, which is measured using a method based on panel data PLS. The population in this research is food and beverage manufacturing companies listed on the Stock Exchange in 2014 until 2016. The sample was determined by the purposive sampling method and obtain 12 companies with the result that, this study obtain 36 sample. Type of data used was secondary data obtained from www.idx.co.idand www.sahamok.com.Based on the results of multiple regression analysis with significance level of 5%, then the results of this study concluded: (1) Institutional ownership does not effect tax avoidance as proxied with current ETR. (2) Managerial ownership has a significant effect on tax avoidance which is proxied with current ETR. (3) The proportion of the Independent Board of Commissioners shall have no effect on the tax avoidance proxyed by current ETR. (4) The audit committee shall have no effect on tax avoidance proxied with current ETR. (5) Audit quality has a significant effect on tax avoidance which is proxied with current ETR.